2013
DOI: 10.1155/2013/175278
|View full text |Cite
|
Sign up to set email alerts
|

Brain Responses to Acupuncture Are Probably Dependent on the Brain Functional Status

Abstract: In recent years, neuroimaging studies of acupuncture have explored extensive aspects of brain responses to acupuncture in finding its underlying mechanisms. Most of these studies have been performed on healthy adults. Only a few studies have been performed on patients with diseases. Brain responses to acupuncture in patients with the same disease at different pathological stages have not been explored, although it may be more important and helpful in uncovering its underlying mechanisms. In the present study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 87 publications
(53 reference statements)
1
20
0
Order By: Relevance
“…We contrasted their alterations in connectivity and the results showed that the alterations were more obvious in contralateral acupoint group even though the direct activation area of contralateral acupuncture was in the non-lesioned side. It was in accordance with clinical result that contralateral acupuncture has stronger therapeutic effect [10,13]. Our results suggested that acupuncture might improve functions of the lesioned side brain by stimulating non-lesioned side brain.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We contrasted their alterations in connectivity and the results showed that the alterations were more obvious in contralateral acupoint group even though the direct activation area of contralateral acupuncture was in the non-lesioned side. It was in accordance with clinical result that contralateral acupuncture has stronger therapeutic effect [10,13]. Our results suggested that acupuncture might improve functions of the lesioned side brain by stimulating non-lesioned side brain.…”
Section: Discussionsupporting
confidence: 91%
“…It has been verified that the acupuncture played an important role in ameliorating the blepharospasm in non-lesioned side [15,16]. We suggested that the alteration in non-lesioned side SI connectivity might be the result of reductions of the abnormal brain activity tendencies [5,10].…”
Section: The Possible Mechanism Of Bilateral Si Connectivity Changesmentioning
confidence: 79%
See 1 more Smart Citation
“…Electroacupuncture intervention activates the nervous system differently in health than in pain, as shown by the fact that opioid receptors are differentially involved in electroacupuncture inhibition of pain in healthy animals and those with persistent pain (table 2), as well as by the brain responses to acupuncture displayed by patients with Bell’s palsy compared to those of healthy volunteers. 183 Moreover, electroacupuncture parameters affect outcomes: 10 Hz electroacupuncture produces longer lasting alleviation of inflammatory pain than does 100 Hz, and 2–10 Hz inhibit nerve injury-caused allodynia/hyperalgesia more potently than does electroacupuncture at 100 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that patients with Bell’s palsy have distinct brain responses to acupuncture treatment compared to healthy volunteers. 183 Further, patients at different stages of Bell’s palsy varied in brain responses to acupuncture. Taken together, electroacupuncture alleviates visceral pain by modulating spinal and DRG activities through endogenous opioids.…”
Section: Visceral Pain Modelsmentioning
confidence: 99%